The New Way to Exercise? Evaluating an Innovative Heart-rate-controlled Exergame - Ketelhut, Sascha; Röglin, Lisa; Kircher, Eva; Martin-Niedecken, AnnaLisa; Ketelhut, Reinhard; Hottenrott, Kuno; Ketelhut, Kerstin (International Journal of Sports Medicine, 2021)
Exergames may offer novel opportunities to expand physical activity. Most games, however, only result in low to moderate-intensity activities that are too low to allow relevant physical adjustments. In the present study, the exercise intensity of a new, heart rate controlled, functional fitness game was assessed. 28 subjects (aged 24.8±3.8 yrs; 46% female; BMI 23.2±2.3 kg/m2) were enrolled in this study. VO2max and maximal heart rate (HRmax) were assessed during a maximal graded exercise test on a treadmill and compared with the oxygen consumption (VO2) and heart rate (HR) during a game in the ExerCube.In the ExerCube, the subjects reached a peak HR of 187.43±9.22 bpm, which corresponds to 96.57±3.64% of their HRmax. The mean HR throughout the game was 167.11±10.94 bpm, corresponding to 86.07±4.33% of HRmax. VO2peak reached 41.57±5.09 ml/kg/min during the game in the ExerCube, which corresponds to 84.75±7.52% of VO2max. The mean VO2 consumption during the game reached 32.39±4.04 ml/kg/min, which corresponds to 66.01±5.09% of VO2max. The ExerCube provides a form of vigorous physical exercise. Due to its playful, immersive, and motivating nature, the ExerCube seems to be a promising tool to facilitate physical activity.
Keywords: serious games; holistic training; high-intensity exercise; personalized; exercise